KARAKTERISTIK AKTIVITAS PEDAGANG KAKI LIMA PADA KAWASAN KOMERSIAL DI PUSAT KOTA Studi Kasus: Simpang Lima, Semarang - Retno Widjajanti (Diponegoro University, 2009)
The characteristic of street vendors in Simpang Lima should be recognized. It is connected with spatial region’sactivity so that both of the formal and informal activities can exists harmonically. The characteristics of thestreet food vendors activity are follows: the activity space (street vendor’s trading location is at the mall/office/school/mosque/ in Pancasila square and they are selling in the sidewalk at the edge of the Pancasila square);their distribution pattern is agglomeration; they are more settle; their activities (type of food/beverage,accessories, clothing, grocery, cigarettes, and their facilities are tent, wagon, carpet, table/rack; the time ofstreet vendors trading is following the formal activities of the region; goals and motivations of visitor’s vendorsis that most of them are visiting street vendors, and the motivational visits are to buy food/drinks and othertypes of merchandise).